Bacterial Metabolism During Biofilm Growth Investigated by 13C Tracing - Wan, Ni; Wang, Hao; Ng, Chun Kiat; Mukherjee, Manisha; Ren, Dacheng; Cao, Bin; Tang, Yinjie J. (Frontiers in Microbiology, 2018)
This study investigate the metabolism of Pseudomonas aeruginosa PAO1 during its biofilm development via microscopy imaging, gene expression analysis, and 13C-labeling. Firstly, dynamic labeling was employed to investigate glucose utilization rate in fresh biofilms (thickness 60 micrometer). The labeling turnover time of glucose-6-P indicated biofilm metabolism was substantially slower than planktonic cells. Secondly, PAO1 was cultured in continuous tubular biofilm reactors or shake flasks. Then 13C-metabolic flux analysis of PAO1 was performed based on the isotopomer patterns of proteinogenic amino acids, which found that these actively-growing biofilm cells largely conserved the flux network as their planktonic mode. Both biofilm and planktonic PAO1 shared following metabolic features. 1. Glucose was catabolized by two cyclic routes (the TCA cycle and the Entner-Doudoroff-Embden-Meyerhof-Parnas loop) that facilitate NAD(P)H supplies. 2. Anaplerotic pathways (including pyruvate shunt) increased flux plasticity. 3. Variations in flux distributions (normalized by glucose uptake rate as 100%) between biofilm cells and planktonic cells were relatively small (less than 20%). 4. qPCR analysis indicated that key genes in fresh biofilm cells showed expression levels comparable to planktonic cells. Thirdly, PAO1, Shewanella oneidensis (as the comparing group), and their c-di-GMP transconjugants (with different biofilm formation capabilities) were 13C-labeled under biofilm reactors or planktonic conditions. Analysis of amino acid labeling variances from different cultures indicated MR-1 flux network was more flexibly changed during the biofilm formations.